WASTE MANAGEMENT IN MAKASSAR CITY: CHALLENGES, POLICIES AND SOLUTIONS - Sirajuddin Sirajuddin; Rika Dwi Ayu Parmitasari; Lince Bulutoding; Rahman Ambo Masse; Trisno Wardy Putra; Ayu Ruqayyah Yunus; Nurfiah Anwar (Jurnal Pengabdian Masyarakat Ekonomi dan Bisnis Digital, 2024)
Waste management in Makassar City is an increasingly pressing issue along with rapid population growth and urbanization. In this context, the main challenges faced are low public awareness, limited waste management infrastructure, and weak enforcement of regulations related to waste processing. This study aims to provide a better understanding to the public about the importance of sustainable waste management and to study waste management policies and practices in Indonesia and Malaysia. Through community service activities including field observations, interviews with stakeholders, counseling, and preparation of recommendations, it is hoped that applicable solutions can be found to overcome waste management problems. One of the proposed solutions is the development of a Waste Bank which functions as a means to manage and recycle waste more effectively. The results of the study indicate that active community participation, government support, and collaboration between various parties are essential to create a sustainable waste management system. The recommendations produced include increasing public awareness, utilizing technology in waste management, and strengthening policies that support community initiatives.